Mitigating Financial Risks in the Transition to a Green Economy: Strategies for Sustainable Development (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines Uzbekistan's transition to a green economy, highlighting key challenges such as limited green finance access, regulatory uncertainties, and the need for international cooperation. It proposes strategic recommendations including establishing a National Green Bank, adopting an integrated policy approach, leveraging global green finance, and supporting green technology R&D. These measures aim to mitigate financial risks, mobilize investments, and ensure Uzbekistan's successful integration into the global green economy, emphasizing the critical role of coordinated efforts among various stakeholders.